Play activity as a means of developing the communicative abilities of primary school children - Voronina N. A. (Pedagogical Technology in the Edauctional System: Innovations and Possibilities, 2021)
A lot of pedagogical and psychological scientific research is devoted to the problem of communication of primary school children. Despite this, this problem is still relevant. Everything around us is constantly changing, life becomes different, human values and priorities change. Modern children are no longer the same as their peers 20-30 years ago. They have a different attitude to the world around them, to their elders, to their peers. How easily a child learns to communicate with people around him, to establish contacts with them, depends on his future educational and working activities. The problem of communication skills of primary school students is also relevant because it is during primary school age that the formation of the child's personality is most intense.
Keywords: коммуникативные способности; младший школьник; game; junior high school student; сверстник; peer; ключевые: игра